An Illuminating Physical View on the Principles of “3 Generations” Structure of Elementary Particles, and on Evolution of Universe–Energy Basic State Field of the Universe (IV) - Xiaodong Yang; Yuchen Yang; Luo Zhen; Yuanbo Bi (Reports in Advances of Physical Sciences)
In this paper, we review the history research on the principles of “3 generations” structure of elementary particles, including Steven Weinberg’s basic physical ideas on the Standard Model of elementary particles, and Barr and Zee’s research and so on. We propose a physical view on the “Dual-production” of quarks and leptons in the evolution of the universe, according to our exiting physical views on the systematic evolution of cosmic and the fundamental theory of EBSF. As for the three generation structure of elementary particles, we propose that the three-generation structure of particle correspond to the evolution of the universe from the plasma quantum state (for the exiting physical phase states of matter formed by the early cosmic evolution, see Y. Xiaodong, Y. Yuchen, L. Zhen and Y. Bi, Rep. Adv. Phys. Sci. 2 (2023) 2250007) to today’s celestial matter, which has undergone three (only three) important physical phase changes in the composition of material structures; that is, each generation of elementary particle structure is the physical elementary phase structure of every stage on condense and sedimentary physical celestial phase. These three stages of condense and sedimentary celestial phase can be simply likened to the three stages of gas, liquid and solid in condensed matter physics, which are essentially formed by the interweaving of cosmic matter formed in the early evolution and the exciters of current-cosmic-evolution EBSF, of course, there is also the complex role of the differentiation inherent time of universe evolution. We analyze that these views not only do not contradict our existing physical theories, but also better understand the nature of its physics and science. The three-generation structure of elementary particles corresponds to a historical epoch in the evolution of the universe, and called the one Mini-era of the domino mechanism before Weinberg’s famous picture <the First Three Minutes>. Although our analysis is somewhat phenomenological, it is still necessary to establish the evolution equation from the plasma state of the early universe to the current physical phase of cosmic celestial matter. More cosmic observation and more experiment data are needed in order to establish the precise quantification of the mathematical physics equations on the evolution process. But we believe that it has a major breakthrough in physical thought, and for the first time, human beings were able to rationally explain the three-generation structure of elementary particles, able to reveal the mystery of the generations of elementary particles in physics.